“This was the best hostel I've ever stayed at!”: exploring service experience in the context of hostels - Araújo, Medéia Veríssimo Silva de (2018)
This thesis aims at exploring the role of service experience in the context of hostels. Although the study has its foundations on tourism field, it is also a multidisciplinary study based on a literature review on the management of experiences, hospitality and services and the knowledge of hostel’s market. Two distinct areas, Brazil and Portugal, were chosen to fundament the empirical study, with Lisbon and Rio de Janeiro as target as they have achieved top-rated hostels awards. To reach the objectives of the research, a comprehensive mixed methods strategy comprising four main research phases was adopted, consisting of 1) a documental analysis on Brazilian and Portuguese reports, legislation and databases 2) an ethnographic fieldwork addressing the so-called successful cases 3) a netnographic analysis of online reviews and 4) a quantitative exploration based on surveys applied to hostels and travellers. The most significant findings contribute to knowledge by: a) bringing empirical evidence on how hostel market develops in distinctive contexts such as Brazil and Portugal; b) identifying and characterizing successful hostels’ practices based on what customers perceive as a positive service experience; c) examining the determinants of a hostel-stay; d) identifying the key features of a positive hostel experience and describe their nature; e) determining the elements on hostels environment that contribute to enhance the customer experience; f) developing a model of enhanced hostel experiences that is of theoretical and practical relevance to contemporary tourism industry. The findings suggest that a hostel experience carries a more symbolic than a utilitarian meaning, especially in relation to its social dimension. Furthermore, they address how some hostels are renouncing a low-quality stigma in order to establish themselves as a ‘cool’ type of tourist accommodation, as they seem to be outlining the future of the sector by redefining the contemporary hostel’s image and attending to modern travellers’ more specific needs. Considering the increasing importance that hostels represent to tourism, this study provides information for scholars and industry practioners interested in how service experience can be enhanced. So, the knowledge generated through this study brings theoretical, empirical and sectorial contributions to tourism field.